A Leukocyte Migration Assay Assists Understanding of Interleukin-1β-Induced Leukocyte Migration Into Preterm Mouse Uterus - Lee, Han; Patel, Vaishvi; Onushko, Meghan; Fang, Xin; Chemtob, Sylvain; Olson, David (Frontiers in Pharmacology, 2022)
Neutrophils and other leukocytes invade the mouse uterus at term birth, which is normal for activating the uterus for labor. To better understand the regulation of this migration at term and interleukin (IL)-1b – induced preterm birth, we developed a mouse leukocyte migration assay (mLMA) and used it with rytvela, an IL-1 receptor allosteric antagonist. The mLMA uses term peripheral blood leukocytes that migrate in a Boyden chamber in response to a chemoattractant. We tested several mouse uterine tissues after homogenization and sedimentation of debris for chemoattractant activity. The most active chemoattractant homogenate came from the mouse lower uterus on gestational day (GD) 18.5. Using flow cytometry, we demonstrated that 99% of the cells that migrate are neutrophils. IL-1b administered on GD 16 stimulated neutrophil migration and invasion into the uterus and the fetal brain along with preterm birth on GD 17. Preterm birth and the increased leukocyte invasion of the maternal uterus and fetal brain were all blocked by the co-administration of rytvela. To test where the site of IL-1b action might be, we examined the potency of lower uterine chemoattractant and the activation of leukocytes following IL-1b +/- rytvela administration. IL-1b did not increase lower uterus homogenate chemoattractant activity, but it significantly (p < 0.05) increased leukocyte activation as defined by cytokine and chemokine expression. Rytvela blocked this activation of leukocytes by IL-1b. We conclude that IL-1b stimulates preterm birth in mice by increasing leukocyte activation leading to increased uterine and fetal brain leukocyte invasion.